2020
DOI: 10.21203/rs.3.rs-17351/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute kidney injury following on-pump or off-pump coronary artery bypass grafting in elderly patients: a retrospective propensity score matching analysis

Abstract: Objectives: This single-centre, retrospective propensity score matching (PSM) study designed to study the impact of cardiopulmonary bypass (CPB) on postoperative acute kidney injury (AKI) and the relationship between AKI and long-term outcomes in elderly patients undergoing coronary artery bypass grafting (CABG). Methods: After PSM, 466 pairs of patients (A group, on-pump; B group, off-pump) who were aged≥70 years undergoing first isolated CABG surgery from January 2012 to December 2016 entered the study. AKI … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…27,29 Similar results were also observed in the octogenarian cohort. 7,14,15,24,30 This is different from our study, which demonstrated an increased incidence of postoperative renal dialysis in the OPCABG group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…27,29 Similar results were also observed in the octogenarian cohort. 7,14,15,24,30 This is different from our study, which demonstrated an increased incidence of postoperative renal dialysis in the OPCABG group.…”
Section: Discussioncontrasting
confidence: 99%
“…The use of cardiopulmonary bypass induced a generalized systemic inflammatory response, nonpulsatile flow, haemodilution, renal hypoperfusion that could lead to a 5%-20% increases in serum creatinine. [22][23][24][25] The incidence of postoperative AKI was higher in patients underwent ONCABG when compared with OPCABG. [26][27][28] However, such effect did not translate into the increased need for dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation